Analysis of Botanical Composition and Potential of Kelakai Leaves (Stenochlaena palustris) of Peat Swamp Plants in Central Kalimantan as Medicinal Plants - Noor Hujjatusnaini; Ema Puspitasari; Astuti Muh Amin (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2022)
Central Kalimantan has a typical peatland habitat which is dominated by Kelakai (Stenochlaena palustris). Various kinds of plants from the Kelakai genus are, for example, the Stenochlaena genus, but the benefits are less known, namely Kelakai. Kelakai is a plant that has clearly visible main characteristics such as stems, roots and leaves. The purpose of this study was to analyze the botanical composition and potency of Kelakai growing on peatlands of Central Kalimantan as a medicinal plant. This research method was an exploratory method supported by laboratory experiments which aimed to determine its potential as a medicinal plant and wound epithelialization under controlled conditions. The data on the botanical composition of Kelakai were analyzed using descriptive analysis, where the sample was obtained by purposive random sampling, while the potency data was analyzed using the Oneway Anova test and then Duncan's 1% test was performed. The wound is on the abdomen 2 cm long. The treatment given was applying Kelakai extract gel with different concentrations on a regular basis every day for 3 days. The results showed that Kelakai on peat swamp land in Central Kalimantan was the most dominant, so it can be concluded that its botanical composition can be a source of forage. The nutritional content of the Kalakai swamp green is quite high, so the Kelakai leaf extract gel has proven potential and can be recommended as an effective wound healing drug at a concentration level of 35%, with the optimal concentration in wound healing at a concentration level of 40%.